OPTIMIZATION OF ISLAMIC RELIGION EDUCATION IN THE DIGITAL AGE: A STUDY ABOUT THE USABILITY OF MOBILE APPLICATIONS LEARNING - Khermarinah (International Journal of Teaching and Learning, 2024)
Islamic education faces the challenge of adapting information technology to improve the quality and accessibility of educational materials. The study aims to explore how mobile learning applications can optimize Islamic religious education in the digital age. Research methods conducted using literary study. The selection criteria include works that explicitly address the use of mobile learning technology in Islamic religious education or have direct implications on this subject. The data collection is focused on studies that cover the design, implementation, and effectiveness of mobile learning applications in the scope of religious education. The analysis is carried out through data synthesis to identify major findings, trends, and gaps in existing literature. Research results show that mobile learning applications offer great potential for optimizing Islamic religious education in the digital age. However, successful implementation requires collaborative efforts from the parties involved to address existing challenges and ensure that these technologies are integrated in a way that supports pedagogical goals.